Constraint effect on corrosion fatigue crack growth behavior of A100 ultrahigh strength steel - LI Yizhe; HUANG Hailiang; BIAN Guixue; WANG Andong; WANG Xi (Journal of Aeronautical Materials)
Ultrahigh strength steel has been widely used to manufacture aircraft landing gear and other load-bearing structures，which is prone to corrosion fatigue failure when serving in harsh marine environment. The fatigue crack propagation behavior of small-sized samples in laboratory is different from that of actual structures due to constraint effect. The fatigue crack propagation tests of A100 ultra-high strength steel in air，neutral and acidic seawater are carried out using single edge tension specimens with different crack depths and specimen thickness. The results show that with the increase of crack depth and sample thickness，the constraint level of crack tip increases，the fatigue crack growth resistance decreases，and the crack growth rate accelerates. The combined effect of constrains and corrosion environment significantly accelerate the fatigue crack growth rate of A100 ultrahigh strength steel. As the amplitude of stress intensity factor ΔK equals to 30 MPa·m1/2，a good positive correlation between constraint parameters and corrosion fatigue crack growth rate can be observed. The relevant research results can provide reference for the service life assessment of ultrahigh strength steel structures in marine environment.